An Analysis of Social-Emotional Development in the Early Childhood Education Process - Damayanti, Shela Dian; Syafril, Syafrimen (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2024)
Delayed social emotional development will have an impact on the difficulty of socializing with the environment. For this reason, proper social emotional development is needed. The aim of the research was to analyse social emotional development in the early childhood education process. This method research was Systematic Literature Review. Data collection used basic Scopus and analysis with Nvivo 12 software. Research results show that social emotional competence in early childhood are social emotional competence (establishing positive relationships with peers, have self-confidence, and collaboration with other people), self-regulation (learn to regulate one's behavior and attention and managing emotions), prosocial behavior (help and entertain others and collaborate with peers), and emotional social behavior (imitate, rivalry, sympathy, empathy, social support, negativism, damage, collaboration, and thinking about yourself). It is believed that research will help teachers in the social emotional development of early childhood according to the child's characteristics.